Carbon Markets Microstructure, Pricing and Policy - Ibikunle, Gbenga (Springer International Publishing, 2018)
This book explores the microstructure of carbon markets and the pricing of carbon financial instruments generally. It provides a critical microstructure analysis of the EU Emissions Trading Scheme (EU-ETS), and also examines the theoretical and related market design issues affecting emissions trading schemes. Individual chapters analyse how intraday pricing evolves in carbon markets, the price impact of block trades in carbon financial instruments and their determinants, short and long-term liquidity effects in carbon markets, and the links between carbon market liquidity and efficiency. The aforementioned issues are explored using case studies of two major trading platforms operating within the EU-ETS. The book concludes by focusing on future policy and regulatory challenges in carbon markets, especially with respect to addressing pricing volatility challenges.